Sebaran Bakteri Coliform Sebagai Indikator Pencemaran Biologis Di Beberapa Sumber AirKecamatan Hu’u, Kabupaten Dompu - Paryono Paryono; Nurliah Nurliah; Ibadur Rahman; Mahardika Rizqi Himawan (LPPM Universitas Mataram, 2023)
Coliform bacteria are a group of bacteria that originate from human and animal feces in large numbers, so they are often used as indicators of food and water quality. This study aims to determine the condition of the aquatic environment based on biological indicators such as the abundance of coliform bacteria in river water and wells in Hu'u sub-district, Dompu district. Data on coliform bacteria and water quality were sourced from PT STM based on the survey results of PT Intertek and PT Sucofindo in several rivers and wells in 2021. The results of data analysis show that most rivers have coliform bacteria density values exceeding the quality standards set by the Ministry of Environment and Ministry of Health. This is probably because many residents and cattle still dispose of their feces in the river.